2020
DOI: 10.1111/ped.14176
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum circulating asprosin levels in children with obesity

Abstract: Background: Childhood obesity is a growing and significant problem worldwide. Asprosin is a novel adipokine that is significantly associated with glucose and insulin production in the liver during fasting. In the present study, we aimed to demonstrate whether there would be differences between obese, overweight, and normal weight children in terms of serum asprosin levels. Methods: Forty-four children with obesity, 54 overweight children, and 60 normal weight children were compared in terms of serum asprosin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
4
29
1
Order By: Relevance
“…However, Wang et al showed that obese children exhibited high levels of asprosin when compared to controls, associating with insulin resistance [ 23 ]. A recent study in Turkish population found similar results [ 44 ]. Intriguingly, there is dramatic discrepancy in circulating levels of asprosin among studies.…”
Section: Discussionsupporting
confidence: 76%
“…However, Wang et al showed that obese children exhibited high levels of asprosin when compared to controls, associating with insulin resistance [ 23 ]. A recent study in Turkish population found similar results [ 44 ]. Intriguingly, there is dramatic discrepancy in circulating levels of asprosin among studies.…”
Section: Discussionsupporting
confidence: 76%
“…Research performed in children reveal controversial results. While Silistre et al as well as Wang et al obtained higher levels of asprosin in children with obesity 19 , 20 as expected, Long et al observed a decrease in asprosin levels in children with obesity when compared with the normal weight control group, but no elucidation was given for these results. 21 …”
Section: Asprosin and Obesity Managementmentioning
confidence: 88%
“…Currently, only little data regarding asprosin levels in pregnant women or children are available. So far, two clinical studies addressed maternal and newborn asprosin levels [3,26] whereas three studies examined serum asprosin in overweight and obese children [16,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…The study did not detect any other significant correlations between asprosin and additional metabolic factors. The authors report asprosin as a marker for childhood obesity and conclude "Further studies are needed to demonstrate the role of asprosin in the etiology of childhood obesity, as well as other diseases that might be associated with effects of asprosin" [21].…”
Section: Introductionmentioning
confidence: 99%